2020
DOI: 10.1097/cji.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Novel DNA-based T-Cell Activator Promotes Rapid T-Cell Activation and Expansion

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We have previously shown that different activation methods affect the proportions of T cell subtypes. 40 We are currently investigating how cells produced in the Prodigy system may differ from CAR T cells produced in bag culture, which could provide insights into whether certain manufacturing platforms are predisposed to a greater sensitivity to cryopreservation. Preliminary results show that cells produced in the Prodigy have a more naive memory cell phenotype, 41 which may be more sensitive to cryopreservation compared with effector memory cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that different activation methods affect the proportions of T cell subtypes. 40 We are currently investigating how cells produced in the Prodigy system may differ from CAR T cells produced in bag culture, which could provide insights into whether certain manufacturing platforms are predisposed to a greater sensitivity to cryopreservation. Preliminary results show that cells produced in the Prodigy have a more naive memory cell phenotype, 41 which may be more sensitive to cryopreservation compared with effector memory cells.…”
Section: Discussionmentioning
confidence: 99%
“…How REP can be improved and refined is still investigated today, for instance with additional medium complements (IL-7, IL-15, anti-CD28 antibodies) but also pre-stimulation with a mix of peptides focusing on pp65 protein, leading to higher proliferation rates in the same culture vessel (Grau-Vorster et al, 2020) (G-Rex flask, see section 7.2). Recent alternatives also include for instance scaffolds mimicking the physiological signal of T cell activation (Zhang et al, 2020), DNAbased platforms to present anti-CD3 and anti-CD28 antibodies (Keskar et al, 2020) or bispecific antibodies (Guo et al, 2020).…”
Section: T Cells: General Considerationsmentioning
confidence: 99%